Efektivitas Penggunaan Media Pembelajaran Animaker Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Matematika Kelas IV Sekolah Dasar - Qonita Izzatun Nisa; Rofita Amelia; Nur Melita Tri Umril Hudaifa; Alfie Rahmi Azida (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Improving the quality of education requires innovation in teaching media, especially for Mathematics, which is often considered difficult by students. This study aims to evaluate the effectiveness of Animaker as a learning medium on the academic performance of fourth-grade students at SD Pelita Hati. A quasi-experimental method with a pretest-posttest control group design was employed. The experimental group used Animaker, while the control group relied on traditional lecture methods. Data were collected through learning achievement tests and analyzed using a t-test. The findings revealed that the experimental group achieved a higher average posttest score (84.85) compared to the control group (77.68), with a statistically significant difference (p < 0.05). In conclusion, Animaker is effective in enhancing students' learning outcomes and creating a more engaging and interactive learning experience.